2016
DOI: 10.1136/bmjopen-2014-007224
|View full text |Cite
|
Sign up to set email alerts
|

Surgical complications and their impact on patients’ psychosocial well-being: a systematic review and meta-analysis

Abstract: ObjectiveSurgical complications may affect patients psychologically due to challenges such as prolonged recovery or long-lasting disability. Psychological distress could further delay patients’ recovery as stress delays wound healing and compromises immunity. This review investigates whether surgical complications adversely affect patients’ postoperative well-being and the duration of this impact.MethodsThe primary data sources were ‘PsychINFO’, ‘EMBASE’ and ‘MEDLINE’ through OvidSP (year 2000 to May 2012). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
114
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(121 citation statements)
references
References 75 publications
3
114
0
4
Order By: Relevance
“…This is an important finding and is consistent with other research on the impact of surgical complications. 18 However, it should be noted that the difference was not clinically significant according to our predefined threshold. The Back and Shoulder Function scale did not detect a similar effect which may be because the complications recorded were largely concerned with damage to the skin surface.…”
Section: Psychometric Analysis Of the Back Appearance Scalementioning
confidence: 99%
See 1 more Smart Citation
“…This is an important finding and is consistent with other research on the impact of surgical complications. 18 However, it should be noted that the difference was not clinically significant according to our predefined threshold. The Back and Shoulder Function scale did not detect a similar effect which may be because the complications recorded were largely concerned with damage to the skin surface.…”
Section: Psychometric Analysis Of the Back Appearance Scalementioning
confidence: 99%
“…However, there is no evidence that the recruited patients differ significantly from those who were not invited to participate. 5 Clinicians can now communicate the frequency of a range of problems associated with LD breast reconstruction surgery to prospective patients and be confident that this information 18 is generalizable and covers the full period of recovery. The findings are reassuring: donor site morbidity following LD reconstruction is limited and similar to that seen with alternative reconstructive options such as a TRAM flap transfer.…”
Section: Psychometric Analysis Of the Back Appearance Scalementioning
confidence: 99%
“…The association between surgical complications and quality of life was the subject of a 2016 systematic review . It found that in two‐thirds of the 50 published studies reviewed, patients who suffered surgical complications had significantly worse quality of life and other psychosocial outcomes than those who had no complications and that this effect persisted in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…Parents who were satisfied with hospital staff communication reported more positive intra-operative experiences whilst other parents described having an excess of overwhelming medical details and information (Hummelinck & Pollock, 2006 For some survivors, the disruption and discomfort experienced as a result of surgery caused long-standing procedural anxiety, triggered by hospital environments and staff. Survivors who described greater pain, immobility and complications following surgery experienced behavioural and psychological impacts to a greater degree than those who did not, reflected by the findings of a recent review of 50 studies (Pinto, Faiz, Davis, Almoudaris, & Vincent, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For some survivors, the disruption and discomfort experienced as a result of surgery caused long-standing procedural anxiety, triggered by hospital environments and staff. Survivors who described greater pain, immobility and complications following surgery experienced behavioural and psychological impacts to a greater degree than those who did not, reflected by the findings of a recent review of 50 studies (Pinto, Faiz, Davis, Almoudaris, & Vincent, 2016).…”
Section: Discussionmentioning
confidence: 99%